Peningkatan Keterampilan Kader Posyandu Melalui Pelatihan dan Asesmen Berbasis Kompetensi - Sugiyanto; Bedjo Santoso; Supriyadi; Esti Handayani; Runjati; Sri Widiyanti; Muflihah Isnawati; Puteri Inandin Nabiha; Rr Sri Endang Pujiastuti; Shinta Dhian Hasna Atifah; Nurul Aeni (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2025)
Posyandu cadres play a strategic role in supporting the transformation of primary health services. However, variations in their abilities in measurement, early detection, health education, and record-keeping remain a challenge. This community engagement program aimed to improve cadre skills through a refresher training based on the five core competencies outlined in the 2024 Ministry of Health Posyandu Cadre Skills Guidelines, while also assessing their competencies. The program was conducted from August to November 2025 in the working area of Puskesmas, Brebes District, involving 91 active cadres from 15 posyandu. A competency-based community empowerment approach was applied using hands-on practice, simulations, and field exercises supervised by health professionals. Skill assessments used structured observation checklists across the five core competency areas. Most cadres were at skill levels equivalent to Purwa to Madya, indicating readiness for formal certification. This competency-based training effectively strengthened cadres’ promotive and preventive skills and is recommended as a tiered training model at the puskesmas level to support primary care transformation indicators and accelerate stunting reduction.